Local Cultural Values In Reading Text Material : A Case Study On English For Nusantara - Putri Indah Sholikhah; Elisa Nurul Laili* (Universitas Nahdlatul Wathan Mataram, 2025)
This study aims to examine the integration of Indonesian local cultural values in reading materials of English for Nusantara from an ethnolinguistic perspective. The background of this research lies in the importance of preserving local culture through contextual and culturally relevant English learning. The ethnolinguistic approach is employed to identify and analyze how local cultural elements are represented in reading texts, including linguistic features, symbolic meanings, and socio-cultural representations. This research applies a case study method with qualitative descriptive analysis on the 9th-grade junior high school English textbook. Data were collected through documentation techniques and analyzed by classifying emerging cultural values such as local wisdom, traditions, arts, and social practices. The results indicate that the textbook contains various local cultural values, including mutual cooperation, politeness, diversity, and heritage preservation; however, their integration remains partial and needs further reinforcement in the context of globalization. These findings are expected to serve as a reference for the development of more inclusive and culturally identity-oriented teaching materials.